1991
DOI: 10.1037/0882-7974.6.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Instantiation of general terms in young and older adults.

Abstract: Instantiation of general terms in discourse requires inference from general world knowledge and use of linguistic context to particularize meaning. According to the semantic deficit hypothesis, older adults should be less likely than young adults to generate or to store such inferences. In Experiments 1 and 2 an indirect measure, relatedness judgment, was used to assess immediate comprehension and memory for inferences. In Experiment 3 a direct measure, cued recall, was used to tap memory for inferences. No ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
6
25
1
Order By: Relevance
“…Further evidence for their use of this information was found in their sensitivity to the verb consistency factor, resulting in an effect of implicit causality. These results suggesting no age differences in the use of contextual information are consistent with a numher of studies (Cohen & Faulkner, 1983;Light & Capps, 1986;Madden, 1988) and with the emerging view that the ability to use this information and make inferences is preserved in old age when the demands placed upon working memory are nùnimal (Burke & Yee, 1984;Light et al, 1982, Light & Alhenson, 1988Light, Valencia-Laver, & Zavis, 1991;Zelinski & Miura, 1990). The following discussion is, therefore, equally applicable to both age groups.…”
Section: Resultssupporting
confidence: 75%
“…Further evidence for their use of this information was found in their sensitivity to the verb consistency factor, resulting in an effect of implicit causality. These results suggesting no age differences in the use of contextual information are consistent with a numher of studies (Cohen & Faulkner, 1983;Light & Capps, 1986;Madden, 1988) and with the emerging view that the ability to use this information and make inferences is preserved in old age when the demands placed upon working memory are nùnimal (Burke & Yee, 1984;Light et al, 1982, Light & Alhenson, 1988Light, Valencia-Laver, & Zavis, 1991;Zelinski & Miura, 1990). The following discussion is, therefore, equally applicable to both age groups.…”
Section: Resultssupporting
confidence: 75%
“…The present study reports greater contextual constraint on representations for older adults than for younger adults, but similar investigations have reported age constancy (Burke & Harrold, 1988;Light et al, 1991). Without further research, we can only speculate about the reasons for this differential finding.…”
Section: Discussioncontrasting
confidence: 53%
“…A study on conceptual instantiation in sentence processing showed no age differences in comprehension and memory for inferences (Light, Valencia-Laver, & Zavis, 1991). Age constancy in sentence comprehension was also demonstrated in activation of relevant aspects of word meanings, such as in 'The oranges rolled off the uneven table' (Burke & Harrold, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…A few studies in the literature, however, have failed to find age differences in context use or other language com-prehension abilities (e.g., Burke & Harrold, 1988;Hopkins et al 1995;Light, Valencia-Laver, & Zavis, 1991). We have argued that context strength, time to process context, and processing efficiency or speed are all important factors determining whether a comprehender will make good use of contextual information during language comprehension.…”
Section: Context Time and Agingmentioning
confidence: 99%